(untitled) (Hematology Meeting Reports, 2009)
Aggressive non-Hodgkin’s lymphoma (NHL) comprises a clinically and biologically heterogeneous group of neoplasms, of which diffuse large B-cell lymphoma (DLBCL) is the most common. The treatment goal for patients with DLBCL is cure with first-line treatment. However, the outlook for patients for many years was grim, with no real advance in treatment options since the 1970s, when cyclophosphamide, doxorubicin, vincristine and prednisolone (CHOP) was held as the best available therapy. The clinical introduction of rituximab has rejuvenated the first-line treatment of DLBCL. Since the landmark GELA-LNH 98.5 study established eight cycles of rituximab in combination with CHOP chemotherapy as the gold standard for all patients with DLBCL, significant improvements in event-free survival and overall survival have been observed. Five-year follow-up data recently demonstrated that the benefit of rituximab is sustained over time. Such is the momentum of research in aggressive NHL that rituximab combined with salvage chemotherapy regimens in relapsed/refractory aggressive NHL has also shown significant improvements in response rates, progression-free survival and overall survival. Furthermore, rituximab-based immunochemotherapy has improved patient outcomes in non-DLBCL aggressive lymphomas, such as mantle cell lymphoma (MCL) and Burkitt’s lymphoma. An important role for rituximab-based maintenance therapy is also emerging, both in DLBCL and MCL. Much further investigation is warranted to fully explore the potential of rituximab-based treatment for patients with all subtypes and stages of aggressive lymphoma. Ongoing large-scale studies such as the GELA’s LNH 03 programme, the CORAL and NHL-13 trials will provide valuable insight into the optimisation of rituximab-based treatment in aggressive NHL.